1980
DOI: 10.1017/s0043174500061506
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Uptake and Transport of 2,4-D and Picloram by Drummond's Goldenweed (Isocoma drummondii)

Abstract: Detached leaves of Drummond's goldenweed [Isocoma drummondii(T. & G.) Greene] absorbed the potassium salt of 2,4-D [(2,4-dichlorophenoxy)acetic acid] from aqueous solutions more slowly than did sunflower (Helianthus annuusL.), and both species absorbed less of the potassium salt of picloram (4-amino-3,5,6-trichloropicolinic acid) than 2,4-D. However, there was no difference in absorption of the herbicides by Drummond's goldenweed leaves after 6 h of exposure to solutions containing 0.5% (v/v) surfactant. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
3
1
Order By: Relevance
“…& A. Gray) Greene] 28 and perennial Glycine species 29 were similar to the absorption pattern observed in both biotypes of prickly lettuce. Studies of auxin resistance in hemp-nettle revealed 50% less acropetal movement of 14 C in MCPA-resistant compared to MCPAsusceptible biotype.…”
Section: ' Results and Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…& A. Gray) Greene] 28 and perennial Glycine species 29 were similar to the absorption pattern observed in both biotypes of prickly lettuce. Studies of auxin resistance in hemp-nettle revealed 50% less acropetal movement of 14 C in MCPA-resistant compared to MCPAsusceptible biotype.…”
Section: ' Results and Discussionsupporting
confidence: 78%
“…Environmental and species effects on absorption and translocation of 2,4-D are well documented. Values for absorption of 2,4-D have varied from 18 to 70% depending upon plant species, study duration, and environmental conditions. For more recent example comparisons, the biphasic absorption of 2,4-D in Drummond’s goldenweed [Isocoma drummondii (Torr. & A.…”
Section: Resultsmentioning
confidence: 99%
“…Absorption 48 h after applied, the herbicide radioactive was 24.26 and 23.81% when used the product alone. Percentage of 2,4-D absorbed by Isocoma drummondii was 12% in 48 h after application in the plant, [11] this value was minor than found in this work. Absorption of propanil in rice was 10.72% of the herbicide applied in 20 min after spraying.…”
Section: Absorption and Translocationcontrasting
confidence: 72%
“…[4] Several researches have been done involving absorption and translocation of 2,4-D in different species as Silene vulgaris (Moench) Garcke, [5] Sisymbrium orientale Torn., [6] Apocynum cannabinum L., [7,8] and Asclepias syriaca L. [8] However, many authors also evaluated absorption and translocation of 2,4-D in association with picloram. Because of this association the control for Euphorbia esula L. [4,9,10] and Isocoma drummondii (T. & G.) has been achieved by Greene [11] with great success as method of control.…”
Section: Introductionmentioning
confidence: 99%
“…The plants of both MO‐Ren and MO‐S biotypes exhibited rapid absorption of [ 14 C] 2,4‐ D and about 70% of the applied herbicide was absorbed within 24 h of treatment. Various environmental, species and application factors can affect 2,4‐ D absorption and previous research has shown that 2,4‐ D absorption can range from 10% to 99% in different species …”
Section: Resultsmentioning
confidence: 99%